Thermal regime effects on the resting metabolic rate of rattlesnakes depend on temperature range - Fabricio-Neto, Ailton [UNESP]; Bueno Gavira, Rodrigo Samuel; Andrade, Denis Vieira [UNESP] (Elsevier B.V., 2019)
While ectothermic organisms often experience considerable circadian variation in body temperature under natural conditions, the study of the effects of temperature on metabolic rates are traditionally based on subjecting animals to constant temperature regimes. Whether data resulting from constant-temperature experiments accurately predicts temperature effects under more natural fluctuating temperature regimes remains uncertain. To address such possibility, we measured the resting metabolic rates of the South American rattlesnakes (Crotalus durissus) under constant and circadian fluctuating thermal regimes in a range of temperatures. Metabolic rates measured at constant 20 degrees C and 25 degrees C did not differ from the rates measured at fluctuating regimes with corresponding mean temperatures. However, the difference between thermal regimes increased with temperature, with the metabolic rate measured at constant 30 degrees C being greater than that measured at the fluctuating thermal regime with corresponding mean temperature. Therefore, our results indicate that thermal regime effects on rattlesnakes' metabolism is dependent on temperature range. Broadly, our results highlight the importance of considering multi-factorial attributes of temperature variation in the exam of its effects over functional traits. Such approach provides a more solid support for inferences about temperature effects on the life history, ecology and conservation of ectothermic organisms.
Keywords: Metabolic rate; Snakes; Circadian variation; Temperature; Thermoperiod; Temperature variability